DEVELOPING EARLY CHILDHOOD COGNITIVE ASPECTS BASED ON ANDERSON AND KRATHWOHL’S TAXONOMY - Laksana, Dek Ngurah Laba; Dhiu, Konstantinus Dua; Jau, Maxima Yohana; Ngonu, Melania Restintuta (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
Developing cognitive learning objectives becomes prior needs to be prepared by teachers. The aspect of early childhood education includes language development, physical-motor, cognitive, socio-emotional, religious-morality, and art. The development of cognitive aspects becomes very important in efforts to develop lesson planning, learning materials, and assessment. This study aims to produce instructional media on cognitive aspects that are appropriate to the characteristics of early childhood education. The instructional media was developed using the research and development design with Rowntree model. The Rowntree development model consists of 3 phases, those are planning phase, development phase, and the evaluation phase. The study was conducted involving 10 early childhood education institutions in Ngada Regency, East Nusa Tenggara, Indonesia. Data was collected by documenting the learning process and utilizing rubrics for assessing the development of cognitive domain. The data were analyzed using descriptive analysis to describe the quality of the products on cognitive domain in early childhood education. The results showed that the development of cognitive aspects in early childhood learning consisted of three aspects, namely aspects of learning and problem solving, aspects of logical thinking, and aspects of symbolic thinking. The development of cognitive aspects in early childhood education for children aged 5-6 years based on Anderson and Krathwohl's Taxonomy produced 18 learning objectives. On the other hand, the development of cognitive aspects in early childhood education aged 4-5 years based on the taxonomy of Anderson and Krathwohl produced 15 learning objectives. The learning objectives of the results of the development had been examined by instructional content experts, instructional design experts, and product user. The test results in the cognitive aspects of learning objectives are in the